The Perspective of Tax Center Digitalization in Strengthening Taxation Socialization: A Case Study at State Polytechnic of Madiun - Tri Septianto; Koerniawan Dwi Wibawa; Ikhwan Baidlowi Sumafta; Imam Mudofir; Meiliyana Susanti (Jurnal Multidisiplin Madani, 2023)
Taxes play an important role as the government's principal revenue to support national development. Tax contributions from taxpayers are essential in funding these programs. However, tax collection faces challenges such as low public awareness, limited access to the latest tax information, low compliance rates, and the tax system's complexity. The Directorate General of Taxes of the Ministry of Finance has launched a Tax Center program on campuses, including at the State Polytechnic of Madiun. Despite being active, Tax Center PNM still uses a conventional approach. Improving service quality is a potential solution to digital transformation. Before implementing digital transformation, a preliminary study is an essential first step. This study discusses the views and perceptions of taxpayers regarding the implementation of digital transformation at Tax Center PNM. The study was conducted through three stages of interviews with ten resource persons: private employees, entrepreneurial students, and government employees. The analysis results show the importance of digital transformation in Tax Center PNM to improve services